Can Early Burkholderia cepacia Complex Infection in Cystic Fibrosis be Eradicated with Antibiotic Therapy? - Horsley, Alex; Webb, Kevin; Bright-Thomas, Rowland; Govan, John; Jones, Andrew M. (Frontiers in Cellular and Infection Microbiology, 2011)
Introduction Organisms of the Burkholderia cepacia complex (BCC) are important pathogens in cystic fibrosis (CF). The majority of those who acquire BCC develop chronic infection but it can also result in rapid decline in a significant minority. In addition, chronic infection with B. cenocepacia in particular is regarded as a contraindication to lung transplantation in many units. Whilst aggressive antibiotic therapy is employed in CF to eradicate Pseudomonas aeruginosa before infection becomes irreversibly established, no formal assessment of such strategies has been previously reported for BCC, despite the apparent widespread adoption of this practice. Methods UK adult CF centres were surveyed about their current approach to new BCC infection. Outcomes of eradication therapy were assessed on patients attending the Manchester Adult CF centre with new BCC isolates between 1st January 2002 and 1st May 2011. Patients with previous infection with the same strain of BCC were excluded. BCC were identified at the national reference laboratories and confirmed by species-specific PCR and RecA sequencing. Results Routine use of therapies to attempt eradication of new BCC is commonly used in the UK (12/17 centres who responded). This typically involves a combination of IV and nebulised antibiotics. Of 19 eligible cases of new BCC infection, the organism has been eradicated in 7 (37%). Three of these did not receive specific eradication therapy. Of 14 patients who have received eradication therapy and completed follow-up, BCC were cleared in only 4 (29%). Conclusions Attempted eradication of new BCC is a common practice in UK adult CF centres. A minority of patients clear the infection spontaneously and the effects of eradication therapies are at best modest. Early treatment may be associated with better outcomes, though there are insufficient data to support the use of any specific treatment regimen. A prospective, systematic evaluation of treatments and outcomes is required